Federalismo do século XXI: paradigmas e desafios: o redesenho do Estado Federal Brasileiro - Santos, Aloysio Vilarino dos (2009)
The objective of the thesis research is to demonstrate the need to change the structure of existing federal state with a new, or proposed to be a "Redesign of the State" because, it was noted during the time that the State is not immune to facts and events (natural or human action), whose concretion requires that the state is able to assimilate them, absorb them and solve them from their existing structure. It is from this perspective that noticed a fragility of our federalism, which requires profound changes in immediate practical and theoretical, structural and legal. The relevance and importance of research, also reside in outline and show that addition of the centralism of the Union, also, an evident abuse in the use of legislative powers between the federal, which, if not completely annulled the powers of other federal entities (Member States and Municipalities) disfigure the Brazilian federalism in a real affront to the Constitution of 1988, against the true spirit of the constituent from which predicted a strengthening of the Brazilian federal state. The third millennium appears with deep sequelae, notably the last century of the second millennium. Eric HOBSBAWM the vision of the past century (XX century) was called as the age of extremes (Age of Extremes: the short twentieth century 1914-1991). It is clear that profound changes occurred in the twentieth century, whose reflections, still, are obvious and noted in the XXI century. The facts and events of the twentieth century have been marked as 2 (two) major World Wars, economic crises, globalization, among others, leaving aside its disastrous effects and damage, also served to show that "the National" and needed Furthermore, should revise its concepts in its various facets, under penalty of died during the twenty-first century. History and other humanities and the social dynamics have shown that the "Economy" is the predominant factor and springboard for the "life in society", therefore, whatever the role of state and leave no part of the aspect economic (micro and macro-economy), because their relationship is direct or interference in the various policies to be adopted (social and non-social), which will be reflected in the state in its entirety. Thus, for the survival of the state itself must be the eyes for the "globe", that is for everything that is happening within the world. The "globalization" in general, is a clear note of the statement above, already in more specific terms it has the "Neoconstitucionalismo. From these two factors some states are changing the way of their decision-making, which should be the tonic current. Thus, the lack of observance of these factors, the follow-making decisions based on the models of the past century without looking at the global, it becomes very dangerous, which shows that there is a need for change and new perspectives. This should be followed, since in 2000 the signatories of the UN (United Nations) are committed to the implementation of "Goals of the Millennium." It is from this picture we notice the need to change or revise the federal model for our state, the change through a new proposal for federalism, it is of vital importance to Brazil, to monitor and to follow the trend current. Moreover, seeking escape from traditional analysis on the topic trying to give a different bias in research, which is bringing to light what the real role of the state, what your real inter-relationship with the Company, which to address this proposal will address issues on "Globalization", and on issues relating to trends that states must follow in relation to development in general, notably on the economic development in view the need for changes in paradigms and crises in the economic sphere, which in truth is the crisis or State therefore has a direct relationship with the model adopted by this or that (s) Member (s). Under internal, or in the case of Brazil this analysis necessarily involves the "economic order" established by the Constitution of 1988, as envisaged in its Title VII, that some of the area of law and also from outside the legal sphere called the "Constitution economy. The focus of this constituent part of the Constitution was to establish a democratic state of law back to the social conditions of life of the majority of the population, as enshrined in the left caput of Article 170: "The economic order, based on the enhancement of human labor and free initiative, aims to ensure decent existence for all, as the dictates of social justice, with the following principles: "Are fundamental objectives outlined in the Constitution of 1988 a cooperative federalism and balance and reduce regional inequalities, whose ultimate purpose is to guarantee citizens the full realization of the common good, which is ultimately the goal is democratic state of law